Accessibility and Inclusion for Families with Children with Autism Spectrum Disorders in Cultural Institutions. (21st July 2022) - Hladik, Libby; Meyer, Robin; Allen, Scott; BONNICI, Sandra; Froelke, Nicole A.; Romaniak, Holly; Ougayour, Yasmeena; Nelson, Nicole; Alkhamees, Abdullah K.; Davis, Heather; Ausderau, Karla K.
Abstract: This project aimed to develop a comprehensive set of evaluation tools to assess the accessibility and inclusion of families with children on the autism spectrum in cultural institutions. A stakeholder team conducted interviews, reviewed museum artifacts, and observed museum programming. An evaluation toolkit was constructed by incorporating best practices from current literature and collected data. Tools were piloted and revised after being implemented in the museum context. The Toolkit to Increase Accessibility and Inclusion for Children on the Autism Spectrum and with Sensory Processing Differences in Cultural Institutions was developed with five unique tools, the Dimensions of Accessibility framework, and further resources to provide a self‐assessment of cultural institutions. The toolkit can be used broadly across many types of institutions and self‐assessment can lead to proactive development of public spaces, institutions, and programming that is accessible and inclusive of diverse groups of people, beyond families with children on the autism spectrum.